The Relationship Between Stress Level and Sleep Paralysis During COVID-19 among Final-Year Nursing Students - Widya Nurwulan Santika Utami; Sukma Senjaya; Hasniatisari Harun; Vira Amelia (Jurnal Berita Ilmu Keperawatan, 2023)
World Health Organization warns that stress will increase due to the COVID-19 pandemic situation. Stress can disrupt sleep quality, and the potential for experiencing sleep paralysis is most common in students, which can reduce students' academic abilities. This study aimed to identify the correlation between stress levels and sleep paralysis in final-year nursing students during COVID-19.; The research design describes the correlation with a Cross-Sectional approach with a total sampling technique of 238 final-year nursing students. Data were analyzed using a chi-square test; Results: with Asymp.Sig 0.012˂0.05, there is a correlation between stress levels and sleep paralysis. More than half of 152 students (63.9%) with moderate stress levels experienced sleep paralysis, a small portion of 41 (17.2%) students with severe stress levels experienced sleep paralysis and students with mild stress levels 15 (6.3%) experienced sleep paralysis; Conclusions: in this study indicate that the highest stress level experiences sleep paralysis at moderate stress levels. Students are expected to further optimize the counseling activities held by the institution, and the institution can provide interventions such as progressive muscle relaxation therapy to reduce stress levels and sleep disturbances.